OPTIMIZING DEVELOPMENTAL EDUCATION EARLY CHILDHOOD COGNITIVE THROUGH GAME EDUCATIVE - Rita Nofianti; Abdi Syahrial Harahap; Adlina Pearl (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Development cognitive is aspect important in the process of growing flower child age early , because become base for ability think logical , solving problems , and adapt to environment learning at the stage next . Research This aim For optimize education development cognitive child age early through implementation game educationally designed in accordance with stage development and characteristics Study child . Approach game educative chosen Because capable give experience active , fun and meaningful learning for children . Research This use method descriptive qualitative with approach studies fields in several Early Childhood Education and Kindergarten institutions , including Nurul Qur'an Kindergarten in Stabat. Data collected through observation , interviews , and documentation to activity learning that uses game educational . Data analysis was carried out with the Miles and Huberman model covering data reduction , data presentation , and data extraction conclusion . Research results show that game educative can increase aspects cognitive child age early , such as ability grouping , recognizing pattern , counting simple , remembering , and develop language and creativity think . The teacher plays a role important in design and facilitate appropriate game with objective learning as well as give appropriate stimulation . In addition , parental involvement in support activity play children at home strengthen results learning in schools . Research This recommend game model development educative contextual based environment local and cultural child For optimize stimulation cognitive . Optimization education child age early through game educative No only increase ability think children , but also form character independent , creative , and collaborative learning.